European Health Union - Fronteira, Inês (2024)
Funding Information: Fundação para a Ciência e Tecnologia for funds to GHTM UID/04413/2020. This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors. Publisher Copyright: © 2023 John Wiley & Sons Ltd.